A díade saberes e práticas docentes : um estudo de suas inter-relações - Sousa, Ana Teresa Silva (2011)
This study The Dyad of knowledge and teaching practices: an inter-relational study deals with the relationship between conceptual knowledge on behalf of the teachers and their teaching practices. The research aims to investigate the relations amongst conceptual meanings related to the professor and the practices of three (03) Fundamental Cycle public schools teachers in Natal-Brazil. Thus, a collaborative research of qualitative nature was performed by us. It was based on collaboration and critical reflection, as well as the socialhistorical theoretical methodological principles of Ferreira (2009). This was acknowledged as an analytical support for the reflections that were realized on concepts related to teachers and teaching considering the archeology on these concepts. The methodological procedures and tools we used consisted of Formative Autobiographies, Reflexive Study, Collaborative Observation, as well as some Reflexive Sessions. The analysis framework was based on information obtained by these methodological procedures as well as the critical collaborative and reflexive procedures. The studies permitted us to widen our knowledge related to the conceptual meaning of teaching and teachers. But it was not always possible for us to (re)elaborate these meanings in the conceptual phase. This was only possible to understand once our Formative Autobiographies were analyzed. They reveal that the concept elaboration process is not a part of our own formative path. The time that was dedicated to that proved to not be enough. The concept elaboration process demands time, effort as well as life-long learning skills. This is not always possible to achieve in this part of the study, on the other hand, this was possible to acknowledge that in the different stages of our conceptual elaboration. The teaching practices that we analyzed were predominantly heterogeneous and were fundamented on meanings of concepts related to teachers and teaching, that were internalized beforehand, (re)elaborated according to the conflicted and contradictory situations. The reflexive and collaborative process that we experimented during the Reflexive Sessions pointed out the predominance of technical and practical reflection process. In some moments it was possible for us to critically reflect on teaching practices due to the collaborative mode that we experienced. The importance of collaboration for teaching formation and professional development of behalf of teachers in general is pointed out by this research. Also regarding this research it was possible to see that there was personal and professional growth, experiencing learning together to collaborative reflect, as well as to counter-argument, reformulate concepts and conceptions aiming to transform our teaching practice